2020
DOI: 10.18632/aging.103478
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circVEGFC accelerates high glucose-induced vascular endothelial cells apoptosis through miR-338-3p/HIF-1α/VEGFA axis

Abstract: More and more findings illustrate the critical roles of circular RNA (circRNA) in diabetes mellitus (DM) and its complications. A major pathological characteristic for DM is the apoptosis of endothelial cells (ECs) induced by high glucose (HG), however, the function of circRNA in the ECs’ phenotypes is still elusive. Here, this study identified an up-regulated circRNA (circVEGFC) in the HG-induced human umbilical vein endothelial cells (HUVECs). Functionally, knockdown of circVEGFC alleviated the apoptosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…CircVEGFC is a novel circRNA with critical functions in high glucose-induced cell injury. 15 It was reported that…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CircVEGFC is a novel circRNA with critical functions in high glucose-induced cell injury. 15 It was reported that…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Circular RNA vascular endothelial growth factor C (circVEGFC) is novel regulator of glucose metabolism. 15 CircVEGFC can promote high glucose-induced injuries of vascular endothelial cells by interacting with the miR-338-3p/HIF-1α/VEGFA axis, 15 while its role in GDM is unknown. This study aimed to detect the expression of circVEGFC in GDM and explore its clinical values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, inhibiting apoptosis-associated endothelial dysfunction may ameliorate dM-induced vascular complications (6)(7)(8). The association between high glucose (HG) stimulation and endothelial apoptosis has been extensively studied (9)(10)(11), as HG is a typical characteristic of dM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cheng et al highlighted that has_circ_0068087 was highly expressed in HG-triggered human umbilical vein endothelial cells (HUVECs) and regulated HG-induced cell dysfunction by acting as an miR-197 sponge ( Cheng et al, 2019 ). Wei et al demonstrated that circRNA vascular endothelial growth factor C (circVEGFC) promoted HG-induced apoptosis in HUVECs through the regulation of miR-338-3p ( Wei et al, 2020 ). Pan et al uncovered that has_circ_0054633 protected HUVECs against HG-induced dysfunction by modulating heme oxygenase-1 (HO-1) expression via sponging miR-218 ( Pan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%